2015
DOI: 10.1089/neu.2014.3733
|View full text |Cite
|
Sign up to set email alerts
|

Facility Characteristics and Inhospital Pediatric Mortality after Severe Traumatic Brain Injury

Abstract: More than 500,000 children sustain a traumatic brain injury (TBI) each year. Previous studies have described significant variation in inhospital mortality after pediatric TBI. The aim of this study was to identify facility-level characteristics independently associated with 30-day inhospital mortality after pediatric severe TBI. We hypothesized that, even after accounting for patient-level characteristics associated with mortality, the characteristics of facilities where patients received care would be associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…Brown and colleagues [ 21 ] demonstrated that among 118,611 Medicare beneficiaries hospitalized for acute myocardial infarction, larger hospitals had a significantly reduced 30-day hospital readmission rate, compared to smaller hospitals. In the pediatric TBI population, it has been shown that hospitals with improved guideline adherence have reduced mortality and improved functional outcomes [ 11 ]; in addition, regional variation in mortality after pediatric TBI has been demonstrated as well [ 22 ]. In our study, we pre-specified facility-level factors in an attempt to adjust for differences in processes of care across facilities, but our hospital characteristics may have only served as a crude proxy and likely did not capture with enough granularity factors such as adherence to guidelines and evidence-based care pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Brown and colleagues [ 21 ] demonstrated that among 118,611 Medicare beneficiaries hospitalized for acute myocardial infarction, larger hospitals had a significantly reduced 30-day hospital readmission rate, compared to smaller hospitals. In the pediatric TBI population, it has been shown that hospitals with improved guideline adherence have reduced mortality and improved functional outcomes [ 11 ]; in addition, regional variation in mortality after pediatric TBI has been demonstrated as well [ 22 ]. In our study, we pre-specified facility-level factors in an attempt to adjust for differences in processes of care across facilities, but our hospital characteristics may have only served as a crude proxy and likely did not capture with enough granularity factors such as adherence to guidelines and evidence-based care pathways.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several recent publications have documented differences in a variety of pediatric TBI outcomes such as discharge to rehabilitation and inpatient mortality by region or state in the United States. 19,20 An additional study described factors that are important for successful recovery for pediatric TBI patients (including identifying at-risk children at the time of injury and receiving follow-up medical, transitional, and educational services). 21 These studies suggest that the availability and adequacy of acute and follow-up care may be quite different in different areas of the country, which could lead to differences in the outcomes of our study.…”
Section: Discussionmentioning
confidence: 99%
“…An approach to study quality of care in hospital units is via a global assessment of culture with a focus on the human resources, organizational structure, patient care management, culture of safety and consistency of approach towards specific issues (e.g. infection control, medication safety, or pain management) [7, 11, 1618]. Therefore, we conducted a global assessment of structure, process, and culture, with specific domains potentially relevant for pediatric TBI.…”
Section: Discussionmentioning
confidence: 99%